2015
DOI: 10.1021/acs.jpclett.5b00654
|View full text |Cite
|
Sign up to set email alerts
|

Residue-Specific Force Field (RSFF2) Improves the Modeling of Conformational Behavior of Peptides and Proteins

Abstract: A recent report of 3JHNHα scalar coupling constants for hundreds of two-residue peptides has provided an important opportunity to test simulation force fields for proteins. Here we compare the abilities of three derivatives of the Amber ff99SB force field to reproduce these data. We report molecular dynamics (MD) simulations of 256 two-residue peptides and show that the recently developed residue-specific force field (RSFF2) produces a dramatic improvement in the agreement with experimental 3JHNHα coupling con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…MD simulations were performed with Gromacs[ 28 ] (version 4.5.4) using the RSFF2 force field[ 29 , 30 ] for the protein and TIP3P water model[ 31 ]. The recently developed residue-specific force fields were found in an independent study to be superior to earlier force fields in the correct reproduction of protein structure and folding[ 32 34 ]. The protein was solvated in a rhombic octahedral box with periodic boundary conditions and a distance of 10 Å between the boundary and the nearest protein atoms.…”
Section: Computational Methodologymentioning
confidence: 99%
“…MD simulations were performed with Gromacs[ 28 ] (version 4.5.4) using the RSFF2 force field[ 29 , 30 ] for the protein and TIP3P water model[ 31 ]. The recently developed residue-specific force fields were found in an independent study to be superior to earlier force fields in the correct reproduction of protein structure and folding[ 32 34 ]. The protein was solvated in a rhombic octahedral box with periodic boundary conditions and a distance of 10 Å between the boundary and the nearest protein atoms.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Ones MD simulations of LC3B monomer were collected starting from the free state NMR structure with PDB entry 1V49 (Kouno et al, 2005). We have employed ten force fields (ff14SB (Maier et al, 2015), ff99SBnmr1 (Li and Brüschweiler, 2010b), ff99SB*-ILDN (Best and Hummer, 2009;Lindorff-Larsen et al, 2010), ff99SB*-ILDN-Q (Best et al, 2012a;Best and Hummer, 2009;Lindorff-Larsen et al, 2010), a99SB-disp (Robustelli et al, 2018), RSFF2 (Li and Elcock, 2015;Zhou et al, 2015), CHARMM22* (Piana et al, 2011), CHARMM27 (Bjelkmar et al, 2010), CHARMM36 (Huang et al, 2017) and RSFF1 (Jiang et al, 2014).…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…ff99SB*-ILDN(Best and Hummer, 2009;Lindorff-Larsen et al, 2010), ff99SB*-ILDN-Q(Best et al, 2012a; Best and Hummer, 2009;Lindorff-Larsen et al, 2010), a99SBdisp(Robustelli et al, 2018), RSFF2(Li and Elcock, 2015;Zhou et al, 2015), CHARMM22*(Piana et al, 2011), CHARMM27(Bjelkmar et al, 2010), CHARMM36(Huang et al, 2017) and RSFF1(Jiang et al, 2014).…”
mentioning
confidence: 99%
“…Our recently developed residue-specific force field RSFF2 50 was used, which is an improvement of AMBER ff99SB 51 by fitting conformational distributions from PDB coil library using residue-specific torsional parameters. [52][53][54] Previous studies have shown that RSFF2 can well reproduce conformational behaviors of peptides and proteins, 55 and predict the crystal structures of cyclic peptides accurately. 20 We first performed MD simulations of a series of target models to find suitable patterns that are related to residue-level model quality.…”
Section: Introductionmentioning
confidence: 99%